The Budapest Museum of Fine Arts - Szépművészeti Múzeum; Garas, Klára, 1919-2017 (Budapest : Corvina, 1988)
Department of Egyption Art - Greek and Roman antiquities - Old masters - Old sculpture - Prints and dwawings - Modern art